Contradictions and Limitations of Final Offer Selection: The Manitoba Experience - Black, Errol; Silver, Jim (Relations industrielles / Industrial Relations, 1990)
This paper analyses Manitoba's experiment with final offer selection for the purpose of clarifying the roots of the conflict it has generated.